A revision of species diversity in the neotropical genus Oreobates (Anura: Strabomantidae), with the description of three new species from the amazonian slopes of the andes - Padial, José (2012)
We revisit species diversity within Oreobates (Anura: Strabomantidae) by combining molecular phylogenetic analyses of the 16S rRNA amphibian barcode fragment with the study of the external morphology of living and preserved specimens. Molecular and morphological evidence support the existence of 23 species within Oreobates, and three additional candidate species (Oreobates sp. [Ca JF809995], Oreobates sp. [Ca EU368903], Oreobates cruralis [Ca EU192295]). We describe and name three new species from the Andean humid montane forests of Departamento Cusco, southern Peru: O. amarakaeri New Species from Río Nusinuscato and Río Mabe, at elevations ranging from 670 to 1000 m in the Andean foothills; O. machiguenga, new species, from Río Kimbiri (1350 m), a small tributary of the Apurimac River, in the western versant of Cordillera Vilcabamba; and O. gemcare, new species, from the Kosipata Valley at elevations ranging from 2400 to 2800 m. The three new species are readily distinguished from all other Oreobates by at least one qualitative morphological character. Three species are transferred to Oreobates from three genera of Strabomantidae: Hypodactylus lundbergi Pristimantis crepitans, and Phrynopus ayacucho (for which the advertisement call, coloration in life, and male characteristics are described for first time). Oreobates simmonsi is transferred to the genus Lynchius. Hylodes verrucosus is considered a junior synonym of Hylodes philippi. In addition, H. philippi is removed from the synonymy of O. quixensis and considered a nomem dubium within Hypodactylus. The inclusion of Phrynopus ayacucho in Oreobates extends the ecological range of the genus to the cold Andean puna. Oreobates is thus distributed from the Amazonian lowlands in southern Colombia to northern Argentina, reaching the Brazilian Atlantic dry forests in eastern Brazil, across an altitudinal range from ca. 100 to 3850 m. © American Museum of Natural History 2012.